2019
DOI: 10.1007/s10811-019-02004-3
|View full text |Cite
|
Sign up to set email alerts
|

A value chain analysis of Malaysia’s seaweed industry

Abstract: A global shortfall in protein supply from capture fisheries has motivated the Malaysian government to revise its aquaculture strategy, focusing on three commodities: seaweed, fish and marine shrimp. However, the performance of the Malaysian aquaculture sector, particularly seaweed production, is poorly documented. This is the first empirical study to undertake a value chain analysis (VCA) of the Malaysian seaweed sector using stakeholder perceptions and secondary data that encompass members of seaweed farming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 13 publications
1
37
0
3
Order By: Relevance
“…The DI of metals for adults was calculated using the following Equation (2): with C metal the mean metals concentration (mg/kg dw) in each sample, C R the consumption rate, and BW the average body weight for an adult population, considered to be 70 kg [ 14 ]. Year 2018 Malaysian fisheries sector data for capture fisheries and aquaculture show respective production of 1.48 million ton and 397,000 metric ton, macroalgae (seaweed) being the major aquaculture contributor (31% by weight) [ 28 ]. The same study reported the export of the majority of seaweed produced in Malaysia to East Asian countries, including China and the Philippines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DI of metals for adults was calculated using the following Equation (2): with C metal the mean metals concentration (mg/kg dw) in each sample, C R the consumption rate, and BW the average body weight for an adult population, considered to be 70 kg [ 14 ]. Year 2018 Malaysian fisheries sector data for capture fisheries and aquaculture show respective production of 1.48 million ton and 397,000 metric ton, macroalgae (seaweed) being the major aquaculture contributor (31% by weight) [ 28 ]. The same study reported the export of the majority of seaweed produced in Malaysia to East Asian countries, including China and the Philippines.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, in order to protect the consumer, regular surveys of toxic metals in seaweeds and estimation of health risk need to be considered. Considering that consumption of food is the major source of heavy metals exposure/bio-accumulation in the body, this study has sought to assess the levels in seaweed of the metals 19 K, 20 Ca, 12 Mg, 82 Pb, 48 Cd, 34 Se, 13 Al, 25 Mn, 29 Cu, 30 Zn, 26 Fe, 33 As, 11 Na, 28 Ni, 24 Cr, 47 Ag, and 14 Si, with use being made of inductively coupled plasma optical emission spectrometry (ICP-OES). An additional aim was to estimate the carcinogenic and noncarcinogenic risks of metals exposures to the Malaysian population/consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve the economic value, seaweeds are made into Semi Refined Carrageenan (SRC), via a process to meet the quality standards of food (food grade) [ 6 ]. The price of seaweed could reach US$ 3.50 to US$ 5.50 per kg once processed into SRC and the value of seaweed carrageenan increases to US$ 9 per kg after Refined Carrageenan (RC) production [ 7 ]. Carrageenan is used in a variety of commercial applications as gelling, thickening, and stabilizing agents, especially in the food, cosmetic and pharmaceutical industries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…La cadena se basa en la subcontratación y en distintos arreglos formales e informales entre compañías, actores independientes e intermediarios de diversa índole, constituyendo "fragmented but linked economic niches" (Tsing 2009: 159). Las compañías que incorporan valor a las algas se apropian de la mayor parte del valor, aun cuando los intermediarios y actores locales son imprescindibles en la cadena productiva (Nor et al 2019;Tsing 2015;Challies & Murray 2010;Topik, Marichal & Frank 2006). En la cúspide del tramo local se sitúan los exportadores, compañías chilenas de tamaño medio-grande, muchas de ellas con participación de capital europeo y, principalmente, japonés o chino.…”
Section: La Cadena De Valor Del Comercio Del Huirounclassified